Management of Physical Education Facilities and Infrastructure - Dewi, Citra; Windoro, Desrio; Pura, Dwi Naomi (Journal of Education Technology, 2021)
The objective of this research is to find out management of physical education facilities and infrastructure. This research is descriptive qualitative approach. Qualitative research is aimed at understanding social phenomena from the perspective of the participants. These participants are people who are interviewed, observed, asked to provide data, opinions, thoughts, and perceptions. The research strategy is flexible, using various combinations of techniques to obtain valid data through the survey. Based on the results of the study, it was found that through   interview showed that: first, planning for physical education learning facilities was carried out based on a needs analysis and determining the priority scale of activities to be carried out, in accordance with the availability of funds and the level of importance. Second, the provision of learning facilities is carried out by prioritizing aspects of function (utility) which refer to the usefulness of these facilities. Related to the real needs of schools. Third, the use of physical education learning facilities in addition to academic activities in the form of teaching and learning in class, is also used to support the implementation of various school activities. Fourth, storage of learning facilities is coordinated by designated personnel. Appointment of personnel with agreed terms